English Teacher’s Perspective on the Practice of Project Based Learning (PBL) Approach in Bengkalis District - Dessy Satria (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The aim of this study is to determine teachers’ perspective on the practice of project-based learning approach in Bengkalis district. The population of the study includes 44 teachers working in the city of Bengkalis , and the sample of the study includes 20 teachers, 19 of whom are male and 1 is female. In this research, survey method has been used. As a data collection instrument, “Developing the Implementation Difficulties Scale for the Project Based Learning” developed by Pektas, Çelik and Köse (2009) has been used. Utilizing the computer program minitab 19, data analysis have been performed. Standard deviation, arithmetic mean, variance, skewness, maximum, minimum, median and percentage were utilized to analyse the data. Observing how the teachers feel about project-based learning, it is clear that the prototype curriculum offers a fresh opportunity to implement this method and the English teacher showed positive attitudes. According to these research findings, it can be suggested that English teacher should further increase the use of internet media in teaching using PBL.Key Words: Project-based learning, teacher practice on PBL, Teachers’ perspective